2021
DOI: 10.3389/fcell.2021.687473
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Immune-Related Signature Predicting Survival Risk and Immune Microenvironment in Gastric Cancer

Abstract: Background: Tumor immune microenvironment plays a vital role in tumorigenesis and progression of gastric cancer (GC), but potent immune biomarkers for predicting the prognosis have not been identified yet.Methods: At first, RNA-sequencing and clinical data from The Cancer Genome Atlas (TCGA) were mined to identify an immune-risk signature using least absolute shrinkage and selection operator (LASSO) regression and multivariate stepwise Cox regression analyses. Furthermore, the risk score of each sample was cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…All these studies aim to find a reliable signature for predicting prognosis, immune cells infiltration and immune response of GC. Dai identified that low-risk patients in their risk model have a higher tumor mutation burden (TMB) score and immunotherapy score than that in high-risk group (Dai et al, 2021), which is similar to our results. Ma established an immune-related lncRNA signature which has a preferable performance in prognosis and immune cell infiltration prediction.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…All these studies aim to find a reliable signature for predicting prognosis, immune cells infiltration and immune response of GC. Dai identified that low-risk patients in their risk model have a higher tumor mutation burden (TMB) score and immunotherapy score than that in high-risk group (Dai et al, 2021), which is similar to our results. Ma established an immune-related lncRNA signature which has a preferable performance in prognosis and immune cell infiltration prediction.…”
Section: Discussionsupporting
confidence: 90%
“…Some noncoding RNAs such as circRNAs and lncRNAs could also act as diagnostic biomarkers or prognostic factors in GC (Yang et al, 2016;Shan et al, 2019). A recent study identified an immune-related signature composed of MAGED1, ACKR3, FZD2, and CTLA4 could be used to predict the prognosis of GC patients (Dai et al, 2021). These molecular analyses have increased our knowledge of GC biology and might provide new insights on GC therapy strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Among these three immune cell types, effector memory CD8 T cells were the only protective factor with a risk coefficient less than zero. Effector memory CD8 T cells have been reported to play a role in IL-15 signaling-related antitumor activity of PD-1 inhibitors, as well as prognosis prediction of gastric cancer, lung cancer and ovarian cancer ( 45 48 ). However, its role in prognosis prediction and cancer recurrence remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…MSI refers to the phenomenon of the appearance of new microsatellite alleles in tumors due to changes in microsatellite length caused by the insertion or deletion of repeat units compared with normal tissues. Recently, in a study on the immune-related signature of gastric cancer, TMB was found to be higher in the low-risk group [31].It has been demonstrated that CNV, TMB, and MSI are associated with poor prognosis of cancer [32,33]. In breast cancer, Xin Jin et al performed a comprehensive analysis of CNV, MSI, and TMB data from TCGA, which resulted in two genetic variation associated.…”
Section: Discussionmentioning
confidence: 99%